2022
DOI: 10.1002/ece3.9121
|View full text |Cite
|
Sign up to set email alerts
|

Dietary characterization of the endangered salt marsh harvest mouse and sympatric rodents using DNA metabarcoding

Abstract: The salt marsh harvest mouse ( Reithrodontomys raviventris ; RERA) is an endangered species endemic to the coastal wetlands of the San Francisco Estuary, California. RERA are specialized to saline coastal wetlands, and their historical range has been severely impacted by landscape conversion and the introduction of non‐native plant and rodent species. A better understanding of their diet is needed to assess habitat quality, particularly in relation to potential competitors. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Other important structural covariates at the mesohabitat scale provided evidence that shorter vegetation comprised the majority of selected habitats. SMHM were similarly associated with pickleweed presence which served as one of the most significant sources of food for the species (Aylward et al., 2022; Smith & Kelt, 2019). Our overall results suggested that microhabitats may offer SMHM temporary resources such as refugia from predation and tides, while mesohabitats offer abundant food to support individuals and populations in the longer term.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other important structural covariates at the mesohabitat scale provided evidence that shorter vegetation comprised the majority of selected habitats. SMHM were similarly associated with pickleweed presence which served as one of the most significant sources of food for the species (Aylward et al., 2022; Smith & Kelt, 2019). Our overall results suggested that microhabitats may offer SMHM temporary resources such as refugia from predation and tides, while mesohabitats offer abundant food to support individuals and populations in the longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research has hypothesized that SMHM utilize taller vegetation for both refugia from inundation at higher tides (tidal wetlands) or seasonal flooding (managed wetlands) and for cover from predators (Fisler, 1965; Marcot et al., 2020; Shellhammer et al., 1982; Smith et al., 2018). They rely on shorter vegetation such as grasses and pickleweed, as well as over 40 other plant and invertebrate species (Aylward et al., 2022; Smith & Kelt, 2019) for food. Microhabitats represent short‐term landscape use (Morris, 1987), but variation in heights of the vegetation may provide value for SMHM over longer periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, further work is needed in additional forest types, ideally with additional replication within forest type. Second, complementing our habitat assessment with dietary studies using stable isotopes (Post 2002;Newsome et al 2007) or DNA metabarcoding from feces (Kartzinel et al 2015;Iwanowicz et al 2016;Aylward et al MS-b) would shed important light on what each species is consuming where they co-occur, as well as in areas of allopatry. Such work is increasingly cost-effective, and recent developments of noninvasive sampling methods (Aylward et al MS-a) make this increasingly attractive.…”
Section: Discussionmentioning
confidence: 99%
“…During the last decade, DNA metabarcoding for dietary analysis has become a popular approach (Taberlet et al., 2018 ), mainly due to its cost efficiency and superior taxonomic resolution compared to morphological methods (da Silva et al., 2019 ; Soininen et al., 2009 ; Valentini et al., 2009 ). Thus, it has become a common method for resolving the diverse diets of small rodents (Aylward et al., 2022 ; Lopes et al., 2020 ; Sato et al., 2019 ; Zhang & Han, 2021 ). DNA metabarcoding also has the potential to provide information about the relative biomass proportions of ingested food via different approaches (Deagle et al., 2019 )—though neither is optimal in every study system (if in any).…”
Section: Introductionmentioning
confidence: 99%